Disparities in access to fertility care: who’s in and who’s out - Isabel Galic, B.A.; Olivia Negris, M.A.; Christopher Warren, Ph.D.; Dannielle Brown, M.H.S.; Alexandria Bozen, B.A.; Tarun Jain, M.D. (F&S Reports, 2021)
Objective: To study the racial and socioeconomic characteristics of women seeking fertility care in a state with mandated insurance coverage for fertility testing and treatment. Design: Cross-sectional, self-administered survey. Setting: Academic fertility center in Illinois. Patient(s): Of 5,000 consecutive fertility care patients, 1,460 completed the survey and were included in the study sample. Intervention(s): None. Main Outcome Measure(s): Details about demographic characteristics and health care access on the basis of patient race/ethnicity and socioeconomic status. Result(s): The mean age of participants was 36.1 years; 75.5% were White, 10.2% Asian, 7.3% Black, 5.7% Latinx, and 1.3% Other. Most women had a bachelor’s (35.5%) or master’s degree (40.5%) and an annual household income of >$100,000 (81.5%). Black and Hispanic women traveled twice as far (median 10 miles) as White and Asian women (median 5 miles for both) for treatment. Black women (14.7%) were more likely to report that their race was a barrier to getting fertility treatment compared with White (0.0%), Hispanic (5.1%), and Asian (5.4%) women. Black and Hispanic women were approximately twice as likely to report income level (26.5% and 20.3%, respectively) and weight (7.8% and 8.9%, respectively) as barriers compared with White and Asian respondents. Conclusion(s): Significant racial and socioeconomic disparities exist among fertility patients accessing care. Beyond providing all Americans with health insurance that covers fertility treatment, further research in the general population is needed to understand the complex social, cultural, racial, and economic factors that prohibit many individuals from accessing needed fertility care.